1987
DOI: 10.1073/pnas.84.17.6215
|View full text |Cite
|
Sign up to set email alerts
|

Recombinational substrates designed to study recombination between unique and repetitive sequences in vivo.

Abstract: Recombinational substrates designed to study recombination between unique and repetitive sequences in vivo (sister-chromatid Contributed by Ronald W. Davis, December 29, 1986 ABSTRACT Three recombination events, reciprocal recombination, sister-chromatid recombination, and gene conversion, were studied using substrates designed in vitro. Each tyje of recombination event can be monitored at any chromosomal location. We have shown that sister-chromatid recombination is induced mitotically by DNA damaging ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 23 publications
4
87
0
Order By: Relevance
“…Consequently, we investigated the epistatic relationship between the rad3-102 and rad27-null mutations with respect to USCR using an assay developed by Fasullo and Davis (1987). The assay monitors the frequency of recombination between 39 and 59 truncated copies of the HIS3 gene that share 300 bp of homologous sequence and are arranged tail to head at the TRP1 locus on chromosome IV.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we investigated the epistatic relationship between the rad3-102 and rad27-null mutations with respect to USCR using an assay developed by Fasullo and Davis (1987). The assay monitors the frequency of recombination between 39 and 59 truncated copies of the HIS3 gene that share 300 bp of homologous sequence and are arranged tail to head at the TRP1 locus on chromosome IV.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of unequal sister-chromatid recombination rates: The rates of unequal sister-chromatid recombination were determined as previously described (Fasullo and Davis 1987). At least five freshly dissected ABX761 segregants (of each genotype) containing the USCR construct and the his3-D200 allele were streaked out for single colonies on YPD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the frequency of sister chromatid exchanges in mph1D cells in a system where recombination between sister chromatids carrying direct truncated his3 repeats, his3-D59 and his3-D39, gives His + colonies (Fasullo and Davis 1987). The results showed that mph1D cells (yGI012) have a 2.5-fold increase (3.0 6 0.3 3 10 À6 ) of unequal intersister exchanges per cell division when compared with wild-type cells (yNN301; 1.2 6 0.5 3 10 À6 ).…”
Section: Mph1 Regulates Crossovers In Allelic and Sister Chromatid Rementioning
confidence: 99%
“…Unequal SCE was measured using a system described by Fasullo and Davis (1987). The rates of spontaneous mitotic SCE were determined by the method of median using 11 independent colonies for each rate calculation.…”
Section: Unequal Sister Chromatid Exchangementioning
confidence: 99%